2009
DOI: 10.3168/jds.2008-1921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spontaneous heating on fiber composition, fiber digestibility, and in situ disappearance kinetics of neutral detergent fiber for alfalfa-orchardgrass hays

Abstract: "Effects of spontaneous heating on fiber composition, fiber digestibility, and in situ disappearance kinetics of neutral detergent fiber for alfalfa-orchardgrass hays" (2009 aBStraCt During 2006 and 2007, forages from 3 individual hay harvests were utilized to assess the effects of spontaneous heating on concentrations of fiber components, 48-h neutral detergent fiber (NDF) digestibility (NDFD), and in situ disappearance kinetics of NDF for large-round bales of mixed alfalfa (Medicago sativa L.) and orchardgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 23 publications
4
30
0
Order By: Relevance
“…The detergentbased methods are a well-established method to measure composition concentrations. Forage quality laboratories and research groups routinely use these methods [1,3,5,6,8,16,22]. Development of near-infrared spectroscopy (NIRS) calibrations based on the detergent-based methods can be used to predict these components in a high-throughput manner.…”
mentioning
confidence: 99%
“…The detergentbased methods are a well-established method to measure composition concentrations. Forage quality laboratories and research groups routinely use these methods [1,3,5,6,8,16,22]. Development of near-infrared spectroscopy (NIRS) calibrations based on the detergent-based methods can be used to predict these components in a high-throughput manner.…”
mentioning
confidence: 99%
“…The more extensive hemicellulose degradation compared to cellulose degradation observed in the stored corn stover in this study is consistent with reported values for both aerobic and anaerobic biomass storage conditions. Cellulose enrichment and reduced hemicellulose levels have been documented in the composition of ensiled corn stover [41] and high moisture hay that selfheated during storage [45]. Increased hemicellulose loss compared to cellulose loss has also been documented for fungally degraded corn stover stored aerobically [46].…”
Section: Chemical Compositional Analysismentioning
confidence: 98%
“…Concentrations of N in ADF and NDF, expressed on a CP basis (ADICP or NDICP), were ascertained by refluxing samples in neutral or acid detergent in an Ankom 200 fiber analyzer (Fairport, NY) as defined by Coblentz and Hoffman, (2009). The residual CP concentration within the respective residues was determined by a combustion technique (AOAC, 1998).…”
Section: Laboratory Analysismentioning
confidence: 99%